(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this article, the creative act is proposed as a communicative exercise in the porosity between the body, the Other, and the Earth. In this scope, creation was investigated as a coextensive cosmopolitical action, a way of weaving conversations with the extra-human, in light of animistic perspectives that, based on other notions of rhythm, produce communicative relationships with otherness. As a space for reflection, trans-specific dialogues were held in the research Conversing with Trees, in which speech was defined as part of a multimodal attention in continuous polyrhythmic flow, in contrast to the cultivation of a frontal and unifocal attention that characterizes anthropocentric forms of communication.